Criminal Liability of Perpetrators in Crypto Ecosystem, the Regulatory Challenges, and Legal Voids in the Criminal Law System in Indonesia - Pambudi Pambudi; Zudan Arief Fakrulloh (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to examine the legal gaps and regulatory challenges in enforcing criminal liability against perpetrators of crimes within Indonesia’s crypto ecosystem, particularly in the context of Decentralized Finance (DeFi), smart contracts, and decentralized digital asset trading platforms. The research employs a normative juridical approach using statutory and conceptual methods. The findings indicate that current criminal law instruments, such as Article 378 of the Criminal Code, Article 28 paragraph (1) of the Electronic Information and Transactions (ITE) Law, Law No. 8 of 2010 on the Prevention and Eradication of Money Laundering (TPPU), and Law No. 10 of 1998 on Banking, are inadequate to address the unique and complex characteristics of crypto-related crimes. These crimes are anonymous, cross-jurisdictional, and difficult to trace due to the absence of centralized authority. As a result, the existing legal framework fails to provide sufficient victim protection and leads to weak law enforcement effectiveness. This legal vacuum also hampers the state's ability to respond to the growing digital threats and creates legal uncertainty in the expanding crypto space. Therefore, this study recommends the formulation of specific criminal regulations that comprehensively define digital assets, legal subjects within decentralized systems, and new criminal offenses relevant to crypto-related conduct. It also calls for the establishment of specialized institutions dedicated to investigating and prosecuting such crimes. These proposed regulations are expected to strengthen the national criminal justice system, making it more adaptive, fair, and effective in addressing the challenges posed by digital transformation.